Die periodischen Märkte des Anlolandes in Südostghana - Frischen, Alfred (ERDKUNDE, 1972)
The periodic markets of Anloland based on the four day cycle reach back at least to the second half of the 18th century. They probably began as supra-local collection and distribution points in a densely settled, richly varied and differingly endowed area with regionally extensive specialised economic activities (fishery in the sea, rivers and lagoons; salt extraction; cassava, maize and vegetable growing in the coastal hinterland). Larger markets with long distance trade connections to the west, east and in particular, the north developed in places with good nodality e. g. Keta, Denu or Dzodze. The currently continuing establishment of periodic markets and their large numbers of visitors show that they are not relicts from the past but, despite recent improvements in transportation, communications and the distribution of goods, play an important role in the economic, cultural and political life of the Anlos.